Development of IoT-based Smart System for Environmental Control and Water Quality Monitoring in Plant Factory - Putra, Guyup Mahardhian Dwi; Dewi, Endang Purnama; Amaliah, Wenny; De Side, Gagassage Nanaluih; Umam, Elpanrizkon; Hardi Kurniawan, Nanda (Teknotan: Jurnal Industri Teknologi Pertanian, 2025)
This research aims to design and implement an IoT-based environmental control and water quality monitoring system in the Plant Factory to improve the efficiency and effectiveness of controlled agricultural management. The research method involves designing hardware with sensors to monitor air temperature, humidity, light intensity, water temperature, pH, and TDS, and actuators in the form of fans for temperature control, which are integrated with the Arduino Cloud IoT platform for real-time monitoring. The results show that the developed system successfully monitors environmental parameters and water quality in real-time. All sensors have a MAPE below 5% and when the system test runs well, the fan is able to cool the factory plant room below 30oC, but there are challenges when verifying sensor data between LCD displays and IoT data that are not correct at certain times. Overall, this IoT-based system is effective in providing temperature monitoring and control data in the Plant Factory room.